Effects of ammonia addition on PAH formation in laminar premixed ethylene flames based on laser-induced fluorescence measurement. (15th December 2020) - Li, Youping; Zhang, Yiran; Zhan, Reggie; Huang, Zhen; Lin, He
Abstract: Due to concerns over pollutant emissions and ever-increasing energy crisis, ammonia as a fuel additive is being considered an effective alternative to control polycyclic aromatic hydrocarbons (PAH) formation. In this study, the effects of NH3 addition on PAH formation were investigated experimentally and numerically in laminar premixed ethylene flames. To investigate the chemical effects of NH3 in flames, the equivalence ratios, dilution ratios, and maximum flame temperatures of all tested flames were kept nearly identical. The axial profiles of fluorescence intensities in all target flames were measured by using the laser-induced fluorescence (LIF) technique. The experimental results demonstrated a strong suppression in the fluorescence intensities of PAHs with the increase of NH3 addition. The model study with a blending mechanism reasonably captured the reduced PAH tendencies with the addition of NH3 in experimental measurements, which indicated that NH3 chemically inhibits the PAH formation in the premixed ethylene flames. Chemical kinetic analysis revealed that the NH3 addition leads to the reduced C2 H2 yield, by which inhibition chemical effects of NH3 addition on PAH formation are realized through the route C2 H2 → C3 H4 –P and C4 H4 → C3 H3 → A1 → PAHs. Reaction pathway analysis showed that although there was no direct interaction between C2 H4 and NH3, the C2 H4 and NH3 chemistry interacted by the competition of H, OH, and O radical pools. Specifically, the relative higher H radical in NH3 -doped flames chemically inhibited the C4 H4 and C3 H4 –P formation. Moreover, the reduced C2 H2 yield in the post-flame region inhibited the PAHs growth process via the HACA route. This study highlights the need for an improved model with detailed hydrocarbon-nitrogen interactions to predict PAH formation accurately in the NH3 /hydrocarbon combustion. Highlights: The effects of ammonia addition on PAH formation in premixed ethylene flames were investigated. The mitigation of PAH formation through ammonia addition proposed a new alternative to control PAH emissions. The LIF and modeling results indicated that NH3 chemically inhibits PAH formation.